IMPROVING COMPETITIVE POWER PRODUCTS BY STRATEGIC ENVIRONMENTAL ANALYSIS: CASE STUDY CREDITS PRODUCTS’ EMPLOYEES OF BANK BPR - Ajibroto, Kunto; Pringgabayu, Dematria (Fakultas Ekonomi, Universitas Negeri Jakarta, 2017)
Strategic environment analysis is part of strategic planning component and is a process to always put the company in a strategic position, so that in its development will always be in a favorable position. By analyzing external factors and internal factors, it will be possible to find out the most appropriate strategy formulation for BPR Bhakti Daya Ekonomi in facing the increasingly fierce competition. The research method used is qualitative with data collection using interview and observation, while for data analysis using SWOT method which also use analysis of EFAS and IFAS. The results of this study indicate that the position of BPR Bhakti Daya Ekonomi for Credit Employees products is located in quadrant IV. In this quadrant the bank is in a position where its internal advantage is relatively more dominant than its weakness. However, in the face of the threat environment is relatively greater than the chances. This means that the bank has a relatively better internal capability to expand its business, especially by utilizing some of its internal strengths.